Antioxidant Activity of Ethanol Extract Combination of Cavendis Banana Peel (Musa acuminata) and Kepok Banana Peel (Musa paradisiaca) Using the DPPH Method - Suhada, Adriyan; Ulya, Tuhfatul; Fardani, Roushandy Asri; Pertiwi, Ajeng Dian; Halid, Idham; Pauzan, Pauzan; Ratulangi, Wulan Ratia; Indriani, Nurul; Ariwidiani, Ni Nyoman; Widyan, Rosnalia; Utami, Evi Fatmi; Novianty, Wanda (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2025)
Banana peels are often considered waste despite being rich in bioactive compounds with potential as natural antioxidants. This study aimed to evaluate the antioxidant activity of an ethanol extract combination of Cavendis banana peel (Musa acuminata) and Kepok banana peel (Musa paradisiaca) using the 1,1-diphenyl-2-picrylhydrazyl (DPPH) method. The extraction process was conducted using 96% ethanol maceration, yielding an extraction efficiency of 9.13%. Phytochemical screening revealed the presence of flavonoids, tannins, saponins, and steroids/terpenoids in the extract. Antioxidant activity was assessed through the DPPH method, resulting in an IC50 value of 6.47 ppm and an AAI value of 5.40, classified as very strong antioxidants. These results are comparable to the positive control (Vitamin C), which had an IC50 value of 6.29 ppm and an AAI value of 5.56. The findings suggest that the ethanol extract combination of Cavendis and Kepok banana peels has significant potential as a natural antioxidant source applicable in the food, pharmaceutical, and cosmetic industries. Recommendations for future research include optimization of extraction methods, isolation of key active compounds, in vivo testing, and functional product formulation development to maximize the extract's potential.